Validity and Reliability of A Wound Suturing Training Tool Perception Questionnaire in Nursing Education - Sulistia Nur; Hartanto Prawibowo; Etanaulia Marsim; Riki Ukhtul Fitri (GLOBAL HEALTH SCIENCE GROUP, 2025)
The use of simulation-based training tools such as suture pads is essential in improving clinical skills among nursing students and professionals. To evaluate their effectiveness, a valid and reliable assessment instrument is required. This study aimed to examine the validity and reliability of a questionnaire designed to assess nurses' perceptions of a wound suturing training tool (suture pad) that simulates human skin characteristics. A descriptive quantitative study was conducted involving 100 nurses, with 50 participants from RSUD Ahmad Yani Metro and 50 from RS Mutiara Hati Pringsewu. The questionnaire consisted of 16 items across four domains: physical and sensory aspects, ease and comfort of use, effectiveness and benefits, and general satisfaction. Validity was tested using Pearson Product-Moment correlation with a significance level of 5% (R table = 0.1946), while reliability was measured using Cronbach’s Alpha. The analysis results showed that 14 out of 16 questionnaire items had R calculated values greater than the R table and significance values less than 0.05, indicating that they were valid. Two items (numbers 14 and 15) were found to be invalid as they did not meet these criteria. The Cronbach’s Alpha value demonstrated a high level of internal consistency, indicating that the questionnaire had good reliability. The developed questionnaire is both valid and reliable for measuring perceptions of suture pad usage in clinical skill training. It can serve as an effective evaluation tool to support the development and refinement of simulation-based learning in nursing education.